Financial market spillovers around the globe - Thomas Dimpfl; Robert C. Jung (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2011)
Financial market spillovers around the globeThis paper investigates the transmission of return and volatility spillovers around the globe. It draws on index futures of three representative indices, namely the Dow Jones Euro Stoxx 50, the S&P 500 and the Nikkei 225. Devolatised returns and realised volatilities are modeled separately using a structural vector autoregressive model, thereby accounting for the particular sequential time structure of the trading venues. Within this framework, we test hypotheses in the spirit of Granger causality tests, investigate the short-run dynamics in the three markets using impulse response functions, and identify leadership effects through variance decomposition. Our key results are as follows. We find weak and shortlived return spillovers, in particular from the USA to Japan. Volatility spillovers are more pronounced and persistent. The information from the home market is most important for both returns and volatilities; the contribution from foreign markets is less pronounced in the case of returns than in the case of volatility. Possible gains in terms of forecasting precision when applying our modelling strategy are illustrated by a forecast evaluation.
urn:nbn:de:gbv:27-20131119-142612-5
Keywords: 330; pillovers; Index Futures; Realized Volatility; Structural VAR model; Börsenkurs; Kapitaleinkommen; Index-Futures; Spillover-Effekt; Internationaler Finanzmarkt; Preiskonvergenz; Schätzung; EU-Staaten; USA; Japan